2017
DOI: 10.3390/ijms18061157
|View full text |Cite
|
Sign up to set email alerts
|

Loss of BAX by miR-365 Promotes Cutaneous Squamous Cell Carcinoma Progression by Suppressing Apoptosis

Abstract: Pro-apoptotic BCL2 associated X (BAX) is traditionally thought to be regulated by anti-apoptotic BCL-2 family members, like BCL2-like 1 (BCL-XL), at the protein level. However, the posttranscriptional regulation of BAX is under explored. In this study, we identified BAX as the novel downstream target of miR-365, which is supported by gain- and loss-of-function studies of onco-miR-365. Loss of BAX by either RNA interference or highly-expressed miR-365 in cells of cutaneous squamous cell carcinoma (CSCC) enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Furthermore, the expression of RETREG1 was negatively regulated by miR-186 in CSCC cells, and restoration of RETREG1 attenuated the effects of miR-186 on CSCC cells. In recent decades, a large number of miRs, including, miR-125b (11), miR-365 (20), miR-205 (21), miR-199a-5p (22), and miR-203 (23) have been identified as key regulators of the development and progression of CSCC and numerous other types of human cancer. For instance, miR-199a-5p induces CSCC cell invasion by suppressing E-cadherin expression (22).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expression of RETREG1 was negatively regulated by miR-186 in CSCC cells, and restoration of RETREG1 attenuated the effects of miR-186 on CSCC cells. In recent decades, a large number of miRs, including, miR-125b (11), miR-365 (20), miR-205 (21), miR-199a-5p (22), and miR-203 (23) have been identified as key regulators of the development and progression of CSCC and numerous other types of human cancer. For instance, miR-199a-5p induces CSCC cell invasion by suppressing E-cadherin expression (22).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 is generally considered to be an anti-apoptotic protein that serves an important role in promoting cellular survival and inhibiting the actions of pro-apoptotic proteins (29). By contrast, Bax is identified as a pro-apoptotic member of the Bcl-2 protein family that stimulates apoptosis by heterodimerizing with Bcl-2 to inhibit its anti-apoptotic function (30). To date, it has been widely reported that the Bcl-2/Bax ratio is a key factor that reflects the degree of cell apoptosis resistance (31).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, dysregulation of miRNA expression has been demonstrated to occur during the development and progression of CSCC and other types of human cancer [17][18][19][20][21]. For instance, inhibition of miR-21 could suppress CSCC cell growth and invasion by targeting two tumor suppressors, PDCD4 and PTEN [22].…”
Section: Discussionmentioning
confidence: 99%